GENERIC NAVAL VESSEL WASTE MANAGEMENT MODEL DEVELOPMENT IN SHIP-LIFE CYCLE ASSESSMENT (SLCA) AND COST (SLCC) - Uğur Buğra ÇELEBİ (Journal of Naval Science and Engineering, 2020)
Naval vessels are exposed to many of the rules and regulations determined by international treaties, there are few studies on life cycle analysis of these ships. The aim of study is to calculate life cycle impacts and cost analysis of two vital parts of a generic warship and investigate the emission reduction by using Life Cycle Assessment (LCA). Two important parts (valve and lubricating oil) of a generic warship are selected and the wastes and emissions of these parts are calculated by using licensed SimaPro software. The whole life cycle of the valve and lubricating oil is considered including transportation and recycling phases. Besides, Life Cycle Cost (LCC) analysis is implemented to the samples to calculate the benefits obtained by using LCA method. LCC is implemented on the system and its resulting total benefits, which is obtained by recycling process, is approximately 46,400 €. The environmental impacts of waste valve and lubricating oil are calculated by the help of licensed SimaPro software. The results show that recycling waste oil recovers the cost of waste oil separator by 30 % per ship.